Left Rostrolateral Prefrontal Cortex Lesions Reduce Suicidal Ideation in Penetrating Traumatic Brain Injury - Pardini, Matteo (CNS Spectr, 2019)
OBJECTIVE: The objective of this study is to evaluate the relationship between suicidal ideation, structural brain damage, and cognitive deficits in patients with penetrating traumatic brain injury (pTBI). METHODS: Vietnam War Veterans (n=142) with pTBI to the prefrontal cortex (PFC) underwent combination of neuropsychological and psychiatric examinations and non-contrast CT brain scan. Patients were divided into suicidal ideation positive (SI+) and suicidal ideation negative (SI-) groups according to the suicidal ideation item of the Beck Depression Inventory. RESULTS: Lesions to the left rostrolateral prefrontal cortex (rlPFC) were associated with a lower risk of suicidal ideation independent of depression and global functioning. Left rlPFC lesion also reduced abstract reasoning skills, which mediated the lesion effects on suicide ideation. CONCLUSION: The left rlPFC plays a crucial role in suicidal ideation independently of depression and global functioning.